2018
DOI: 10.1111/jog.13620
|View full text |Cite
|
Sign up to set email alerts
|

Effect of prolonged hospitalization for threatened preterm labor on maternal and fetal vitamin D levels

Abstract: Prolonged hospitalization for TPL reduced the maternal vitamin D status but did not influence the neonatal status at delivery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…The assessment criteria for vitamin D deficiency/insufficiency proposed by the expert panel was as follows: 25(OH)D equal to or above 30 ng/mL was considered to be vitamin D sufficient; 25(OH)D less than 30 ng/mL but not less than 20 ng/mL was considered to be vitamin D insufficient; 25(OH)D less than 20 ng/mL was considered to be vitamin D deficient. Low maternal 25(OH)D has been reported among Japanese pregnant women [17][18][19][20][21][22][23], even though the assessment criteria for vitamin D deficiency/insufficiency among pregnant women has not been defined yet. The proposed assessment criteria have mentioned that different criteria may be needed for pregnant women.…”
Section: Introductionmentioning
confidence: 99%
“…The assessment criteria for vitamin D deficiency/insufficiency proposed by the expert panel was as follows: 25(OH)D equal to or above 30 ng/mL was considered to be vitamin D sufficient; 25(OH)D less than 30 ng/mL but not less than 20 ng/mL was considered to be vitamin D insufficient; 25(OH)D less than 20 ng/mL was considered to be vitamin D deficient. Low maternal 25(OH)D has been reported among Japanese pregnant women [17][18][19][20][21][22][23], even though the assessment criteria for vitamin D deficiency/insufficiency among pregnant women has not been defined yet. The proposed assessment criteria have mentioned that different criteria may be needed for pregnant women.…”
Section: Introductionmentioning
confidence: 99%
“…This study confirmed the results of two studies conducted in Japan which suggested that the prevalence of vitamin D deficiency was high. [10][11][12][13][14][15][16][17] To the best of our knowledge, this study is the first large sample size study which investigated vitamin D levels during pregnancy throughout 1 year in Japan, specifically looking into the effectiveness of the antenatal health guidance intervention for vitamin D insufficiency level to the pregnant women.…”
Section: Discussionmentioning
confidence: 99%
“…Maternal vitamin D deficiency has been linked with multiple adverse maternal and neonatal outcomes, such as hypertensive disorder of pregnancy, 3,4 gestational diabetes, 5,6 preterm birth, 7 and small gestational age of the infants 8,9 . Vitamin D deficiency in pregnant women is a global problem, and a Japanese survey also reported that the proportion of vitamin D deficiency is high in Japanese pregnant females 10–17 . Some countries recommend the use of vitamin D supplements, 18,19 but it is not recommended in Japan, and no guidelines for the screening and supplementation of vitamin D during pregnancy are there.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vitamin D is a fat-soluble vitamin essential for the absorption of calcium from the intestine, thus playing an important role in the musculoskeletal function (10). Vitamin D deficiency during pregnancy is associated with an increased risk of developing maternal gestational diabetes, preeclampsia, recurrent abortions, as well as low birth weight (LBW), and intrauterine growth restriction (IUGR) of the fetus (1,6), which can lead to preterm delivery (11). Vitamin D deficiency is common in premature neonates (12).…”
Section: Introductionmentioning
confidence: 99%